Kesiapan Mental Pemain Persigar Garut Menjelang Liga 4 Seri 1 Jawa Barat Musim 2024/2025 - Farhan Ramadito, Daffa Muchammad; Permadi, Asep Angga; Kosasih, Alam Hadi (Jurnal Porkes, 2025)
This study aims to analyze the mental readiness of Persigar Garut players in facing the 2024/2025 West Java league 4 series 1 competition. The research method used is quantitative descriptive with a survey approach. The research population consists of all Persigar Garut players, with a sample of 25 players selected using purposive sampling. The instrument used is the mental skills test-football questionnaire (MST-F) to measure players' mental resilience. The validity of the instrument was tested using Pearson's product-moment correlation, while reliability was assessed using Cronbach's alpha, yielding a result of 0.983. The results showed that the average mental readiness score of the players was 86.417 with a standard deviation of 4.475. Sixty-four percent of the players had adequate mental readiness, 23% had very good mental readiness, and 14% still needed improvement. These findings confirm that mental resilience contributes to the consistency of athletes' performance under competitive pressure. Therefore, mental strengthening programs such as high-pressure match simulations and relaxation techniques are recommended to enhance players' mental readiness. It is concluded that the mental readiness of Persigar Garut players in preparing for the 2024/2025 West Java series 1 league 4 is generally categorized as good to very good.